Implementation of IoT based vehicle theft detection and accident monitoring system using Arduino - Manogna N, Krishna; Chandra Y, Jeevan; Ratnam Kolluru, Venkata (International Journal of Engineering and Technology, 2018)
This paper presents an efficient system which detects the vehicle accident and sends intimation to the registered mobile numbers such as ambulance or vehicle owner or police etc. IOT based vehicle tracking system detect the Accidents and it sends the position of the vehicle to the specified or pre-programmed mobile number as an SMS. Not only prohibited the accidents. It also prevents the vehicle from theft. If we want opening the door of the vehicle then we need to press a button. Now the owner of the vehicle gets an SMS to grant access. The door will be opened after the authentication only. If an unknown one tries to open the door of the vehicle then you can restrict that person by using mobile. The GPS is used for tracking the vehicle in this system. If any accident detected then an alert will be given with buzzer. Now the driver can press button to stop that. If it is small accident, here the driver can stop the buzzer if the vehicle is safe with in time period. Otherwise an alert will be sent to the owner of the car. It indicates that the person in car or car in trouble.